Civil Litigation In Malaysia : A Practical Guide To Drafting Pleadings - Shahrul Mizan Ismail, Yusfarizal Yussoff (International Books Law Services, 2016)
combines the principles of litigatrion practice with practical applications that are geare especialy to the needs of law students and young legal practitioners who are new to the world of civil litigation.